A Linear Active Disturbance Rejection Control Approach to Position Synchronization Control for Networked Interconnected Motion System - Wang, Yao-Wei; Zhang, Wen-An; Yu, Li (IEEE transactions on control of network systems, 2020)
This article investigates the position synchronization control problem for networked interconnected motion systems (NIMSs). First, a position synchronization error model is established for the interconnected motion system, and the delay-induced uncertainty; the adjacent coupling between subsystems and the external disturbances is lumped together as a total disturbance in the system model. Next, the linear extended state observer (LESO) is designed to estimate the total disturbance and the system state simultaneously. Then, a LESO-based synchronization controller is designed to achieve both position synchronization and disturbance rejection. The effect of the network-induced delay in the synchronization performance is significantly reduced. Finally, experiments on a position synchronization control platform of an interconnected four-motor system are presented to demonstrate the effectiveness and superiority of the proposed method.